Strategies for the Provision of Safe Clothing for Infants in Imo State - P .E, Ozor; R.A., Ohaka (Journal of Home Economics Research, 2024)
This study identified the strategies for the provision of safe clothing for infants in Imo State. It answered two research questions and tested two null hypotheses. The Area of the study was Imo State. Population was made up of 354 literate and 400 non-literate mothers of child-bearing age from three senatorial zones of Imo State. The instrument for data collection was questionnaire. Data were analyzed using mean, standard deviation and t- test. The findings of the study include 14 problems mothers encounter in the provision of safe clothing for their infants and 13 enhancement strategies for the provision of infants clothing. Based on the findings, recommendations were made, including establishing programmes for helping mothers acquire knowledge on the safe clothing provision strategies for their infants.